IBM Analisis Nilai Tambah dan Strategi Pengembangan Agro Industri Susu Olahan di Kabupaten Bogor - Nurhayati, Immas; Suharti, Titing (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
The main purpose of Ipteks bagi Masyarakat (IbM) program is to increase knowledge and skill of farmers (group of cattle ranchers) to change fresh milk to other dairies like yoghurt and pasteurisation of milk and the ability of management and finance. We expect this program can give economic value added, job opportunity for communities around the village and improve farmers welfare. Now, a group of cattle ranchers named “Makmur” has been able to produce yoghurt and pasteurisation of milk continuously branded as YOMA YOGHURT. This product is now being distributed to many school cafetaria and shops around the village. Our analysis informs that this dairy production can increase farmer’s revenue five time higher than before. Everyday, one of organization committees write all the flow of cash in and cash out to know how is the progress of this business day to day and also for transparency and finance accountability.